The Role of Microteaching in Increasing Self-Confidence of UMMY Economic Education Students - Silvi May Nofrin (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This research aims to explore the role of microteaching in increasing the self-confidence of prospective teachers. Microteaching is a learning method that involves teaching simulations on a small scale, where students practice their teaching skills in the presence of a small group of peers or mentors. The method used is the literature method by identifying and analyzing findings from previous research which highlight the relationship between microteaching and increasing self-confidence. Through collecting data from various literature sources such as scientific journals, textbooks, and research reports, researchers can formulate strong arguments regarding the positive impact of microteaching on the self-confidence of prospective teachers..